Electrical direct current stimulation affects retinal vessel diameter and vasodilation in healthy subjects - Freitag, S.; Klee, S.; Haueisen, J. (Acta ophthalmologica (Oxford, England), 2017)
Purpose Electrical stimulation (ES) of the human eye is an emerging technique in the treatment of ophthalmic diseases since several studies showed improvements of visual functions in patients. Neuroprotective effects are assumed to cause beneficial impacts of ES. We investigated the acute effects of ES on retinal vasculature in healthy subjects using dynamic vessel analysis (DVA). This method enables continuous measurements of vessel diameters and assessment of flicker‐induced vasodilation. Methods DVA was performed in 7 healthy subjects (5 females, 25.7±1.7 years, one eye) to examine retinal vessel behavior. Two primary vessel segments were analyzed in each eye (temporal artery (tA) and vein (tV)) regarding baseline vessel diameter (BLD) and vasodilation provoked by flicker (VD). For non‐invasive ES a ring‐shaped rubber electrode surrounding the eye and a square rubber electrode at the occiput were used. Positive direct current (800μA) was applied for 20min at the eye. Each subject participated in two experimental trials in random order, applying real and sham ES (rES/sES) once. DVA was conducted before and immediately after rES/sES to observe changes in BLD and VD. Results were analyzed using paired t‐test to check for changes in BLD and VD due to rES/sES on a level of p=0.05. Results All subjects showed retinal vessel reactions to flicker in DVA. BLD decreased significantly after rES for tA (‐3.4±1.7%; p=0.003) but not for tV (‐0.2±1.6%; p=0.814). In contrast, VD of tA showed an upward trend (+0.7±1.2%; p=0.162), while VD of tV was reduced after rES (‐0.4±1.6%; p=0.547). For sES no significant changes of BLD and VD were observed. Conclusions Real ES affects both arterial BLD and VD by narrowing tA in resting state and enhancing vessel reaction to flicker provocation. These results provide evidences for beneficial effects of ES on circulatory processes.